Kapasitas Lentur Balok Beton Bertulang dengan Styrofoam Sebagai Pengganti Agregat Kasar - Suarnita, I Wayan (SMARTek, 2005)
Requirement of concrete for structure in civil works increase in recent years, that is need more concrete technology. Mixing aggregate with Styrofoam, will produce lightweight concrete    which is mixed with aggregate, concrete light in weight. With low density of concrete, the weight of structure can be reduced which will reduce the basic seismic force of the structure; the such sophisticate will minimized the effect of earthquake’s damage. Result from tests of concrete give average value of compression strength of concrete cylinder (fc’) = 1.6 MPa, modulus of elasticity (Ec) = 443 MPa, and specific gravity = 727. The average yield stress (fy) of the16 mm deformed steel bar and the 8 mm non deformed steel bars were 512 MPa and 370 MPa, respectively. The analizys shows that nominal moment capacity (Mn) of the beams is not increased along with the addition of tension reinforcement since the failure of the beam was caused by bond failure between shear reinforcement bars and the surrounding concrete. The existing crack contour is the shear crack is focusing at the areas that have an initial crack. This crack becomes wide along increasing loading up to failure of the beam.